12.9k views
5 votes
If f(x)=x^2+1 and g(x)=3x+1, find [f(2)-g(1)]^2

User Porusan
by
5.0k points

1 Answer

3 votes

Answer:

[f(2) - g(1)]² = 1

Explanation:

Using the given functions:

f(x) = x² + 1

g(x) = 3x + 1

We can use the given values of 'x' to solve each function and then the combined function. f(2) means the value of 'x' =2 and g(1) means the value of x=1:

f(2) = 2² + 1 = 4 + 1 = 5

g(1) = 3(1) + 1 = 4

[f(2) - g(1)]² = (5 - 4)² = 1² = 1

User Azazul
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.